Performance evaluation of a laboratory-scale Pelton turbine under variable nozzle distance and valve opening - Aini Lostari; Didik Sugiono; Miftahul Ulum; Umi Kulsum; Yudi Hartono (Politeknik Negeri Lhokseumawe, 2026)
Pelton turbines are impulse turbines widely used in micro-hydro power systems operating under high-head and low-flow conditions. Their performance depends strongly on the quality of the water jet impacting the runner buckets, which is influenced by nozzle distance and valve opening. This study experimentally investigated the effects of nozzle distance (60, 70, and 80 mm) and valve opening (30°, 60°, and 90°) on the hydraulic power, turbine power, electrical power, and efficiency of a laboratory-scale Pelton turbine. Turbine rotational speed was measured using a tachometer, while voltage and current were measured using a multimeter to determine power output. The results showed that increasing the valve opening increased hydraulic, turbine, and electrical power due to higher flow rate and jet kinetic energy. However, the turbine efficiency showed non-linear behavior because it was influenced by the quality of the jet and the effectiveness of momentum transfer. The maximum turbine power of 10.52 Watts and electrical power of 10.58 Watts were obtained at a nozzle spacing of 80 mm and a valve opening of 90°. Meanwhile, optimum efficiency was achieved at a nozzle distance of 80 mm and a valve opening of 30%, indicating that optimum conditions do not always occur at maximum flow. The results of this study indicate that the combination of nozzle distance and valve opening significantly influences Pelton turbine performance and is important for optimizing laboratory-scale micro-hydro systems.